Understanding Spirituality in Avatar: The Last Airbender - Hendi Supriatna; Bambang Qomaruzzaman; Dadang Darmawan (UIN Sunan Gunung Djati Bandung, 2026)
This study aims to explore and describe the spiritual meaning in the animated series Avatar: The Last Airbender using James Fowler's theory of spiritual development. In this series, the elements of fire, water, air, and earth are used to illustrate the spiritual journeys of its characters. Fire, as a symbol of love, strength, and transformation, is evident in Zuko's journey, reaching the Reflective-Individualistic stage where he chooses the path of goodness, and in Aang's decision not to kill Ozai, reflecting the Conjunctive Faith stage that transcends rational thought. Water, as a symbol of life and emotion, is represented by Aang, who initially flees from his responsibilities, residing in the Conventional-Synthetic stage before eventually accepting his destiny as the Avatar. Air, symbolizing freedom and intelligence, demonstrates Aang's journey in understanding opposing elements literally at the Mythic-Literal stage. Earth, symbolizing stability and resilience, is reflected in the struggles of Aang and his friends, who reach the Universalizing stage, seeing all humanity as one and committing to the common good. This research employs a qualitative method with descriptive analysis, collecting data through literature studies that include the analysis of written texts, episodes of the animated series, and related literature. The results of this study show how the narrative and symbolism in Avatar: The Last Airbender can teach profound spiritual values, offering new insights into the study of popular culture and spirituality. Through popular media, this research aims to be an effective tool in conveying and teaching spiritual values, helping individuals find inspiration and guidance in their spiritual journeys.